Diabetes and COVID-19 Pandemic: A Potential Mechanisms: A Review - Hind Shakir Ahmed1 , Hiba Shakir Ahmed2 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Diabetes is the greatest public condition among patients with coronavirus disease and has been found toaffect prognosis worldwide. It is revealed that hyperglycemia is one of the elements that elevates the risk ofconsequences in these persons. This study designed to analysis the overall features of the novel coronavirusand provide an understanding of the coronavirus disease in diabetic patients, and its treatment.These patients are usually treated with various medications and this review clarify the role of metforminand dipeptidyl peptidase 4 inhibitors as helpful factors in these patients. Recommendations are made onthe probable pathophysiological mechanisms of the association between coronavirus and diabetes, and itsmanagement. Additional study about this association and its clinical managing is necessary